(untitled) (Advances in Systems Science and Applications, 2024)
This article proposes a control algorithm for an automotive suspension system to improve ride comfort. The control method is based on the combination of Sliding Mode Control (SMC) and Proportional-Integral-Derivative (PID), with parameters optimally selected by an inloop algorithm called OSMCPID. The system’s performance is evaluated by simulation, which goes through three specific cases. According to the article’s findings, in the first two cases, the average value of vehicle body displacement when using the proposed algorithm is only 7.71% and 6.96%, respectively, compared to mechanical suspension. In the third case, vehicle body displacement approaches zero once the road excitation signal ends. Meanwhile, the remaining cases have a more significant gap. In addition, the phase difference of the control signal is slight, while the chattering phenomenon almost does not occur when using the hybrid algorithm. In general, the system can adapt to changing external conditions.